2021
DOI: 10.1002/jcsm.12662
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of diabetes‐induced inflammation mediated pyroptosis, sarcopenia, and adverse muscle remodelling by bone morphogenetic protein‐7

Abstract: Background Diabetic myopathy involves hyperglycaemia and inflammation that causes skeletal muscle dysfunction; however, the potential cellular mechanisms that occur between hyperglycaemia and inflammation, which induces sarcopenia, and muscle dysfunction remain unknown. In this study, we investigated hyperglycaemia-induced inflammation mediating high-mobility group box 1 activation, which is involved in a novel form of cell death, pyroptosis, diabetic sarcopenia, atrophy, and adverse muscle remodelling. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 80 publications
(217 reference statements)
4
60
0
Order By: Relevance
“…HMGB1/TLR4/NF-κB signaling is also related to the upregulation of NLRP3 inflammasome formation [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…HMGB1/TLR4/NF-κB signaling is also related to the upregulation of NLRP3 inflammasome formation [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of caspase-1, secretion of IL-1β (facilitated by caspase-1), and increased substrate of GSDMD, are frequently reported in bacterial infection-related pyroptosis [ 48 ] and sterile inflammation [ 49 ]. Thus, these factors were used as markers of pyroptosis [ 23 ]. Diabetes, a sterile inflammatory condition, is related to increased pyroptosis, characterized by increased caspase-1, IL-1β, and GSDMD in skeletal muscle [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of NLRP3 inflammasome triggers Caspase-1-dependent pyroptosis accompanied by the release of inflammatory factors, such as interleukin (IL)−1β and IL-18 [ 13 ]. Recent studies have demonstrated that pyroptosis may play an important role in the pathogenesis of muscle loss and weakness [ 14 ]. However, the mechanism to which pyroptosis contributes to the atrophy of skeletal muscle induced by dexamethasone remains unclear.…”
Section: Introductionmentioning
confidence: 99%